2014
DOI: 10.1186/1756-8722-7-41
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for thalidomide/bortezomib-induced peripheral neuropathy in multiple myeloma: a feasibility study

Abstract: BackgroundThis single-arm study evaluated feasibility, safety, and initial efficacy of electroacupuncture for thalidomide/bortezomib-induced peripheral neuropathy (PN) in cancer patients with multiple myeloma.MethodsPatients with neuropathy ≥ grade 2 received 20 acupuncture treatments over 9 weeks.ResultsFor the 19 evaluable patients, Functional Assessment of Cancer Therapy/Gynecological Oncology Group-Neurotoxicity (FACT/GOG/NTX) mean (SD) scores improved significantly between baseline and week 13 (20.8 [9.6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 32 publications
1
56
0
1
Order By: Relevance
“…In another pilot study by Bao et al [66], 27 multiple myeloma patients with moderate to severe bortezomib-induced peripheral neuropathy experienced significantly reduced neuropathic pain and improved functioning following 10 weeks of acupuncture treatment (twice weekly for 2 weeks, once weekly for 4 weeks, and then biweekly for 4 weeks). Another single-arm study by Garcia et al [67] demonstrated that electroacupuncture was safe and possibly effective in treating thalidomide/bortezomib-induced peripheral neuropathy in 19 multiple myeloma patients with significant improvements in Functional Assessment of Cancer therapy-neurotoxicity score after 9 weeks treatment. The intervention was conducted over a 9-week period of 20 acupuncture sessions at 2–3 times weekly.…”
Section: Resultsmentioning
confidence: 99%
“…In another pilot study by Bao et al [66], 27 multiple myeloma patients with moderate to severe bortezomib-induced peripheral neuropathy experienced significantly reduced neuropathic pain and improved functioning following 10 weeks of acupuncture treatment (twice weekly for 2 weeks, once weekly for 4 weeks, and then biweekly for 4 weeks). Another single-arm study by Garcia et al [67] demonstrated that electroacupuncture was safe and possibly effective in treating thalidomide/bortezomib-induced peripheral neuropathy in 19 multiple myeloma patients with significant improvements in Functional Assessment of Cancer therapy-neurotoxicity score after 9 weeks treatment. The intervention was conducted over a 9-week period of 20 acupuncture sessions at 2–3 times weekly.…”
Section: Resultsmentioning
confidence: 99%
“…Additional management strategies include use of supportive care medications such as gabapentin, pregabalin, and tricyclics as well as duloxetine, which has the strongest phase III data supporting its use (although not specifically for these chemotherapy classes) . One feasibility study with electroacupuncture in patients experiencing thalidomide or bortezomib‐induced peripheral neuropathy showed promising results which will need to be replicated in a randomized larger study . Several additional small trials have also investigated the benefits of neuropathy in CIPN due to various agents with inconsistent methodologies and results although it does appear that this intervention can be helpful to some patients .…”
Section: Treatment Optionsmentioning
confidence: 99%
“…In addition, a case series has proven the efficacy of body acupuncture in treating patients with CIPN [20], and a pilot study demonstrated that acupuncture improved nerve conduction in peripheral neuropathy [21]. In recent studies, statistically and clinically significant reductions in subjective measurements of bortezomib-induced peripheral neuropathy (BIPN) were observed after acupuncture treatment [22, 23]. However, to date, there have been no randomized controlled clinical research to analyze the effectiveness of acupuncture in treating CIPN of MM patients.…”
Section: Introductionmentioning
confidence: 99%